Tera-Hertz Counterparts to Fast Radio Bursts from Coherent Cherenkov Radiation by Tilted Bunches - Ze-Nan Liu; Wei-Yang Wang; Yu-Chen Huang; Zi-Gao Dai (The Astrophysical Journal)
Fast radio bursts (FRBs) are millisecond-duration extragalactic transients characterized by ultrahigh brightness temperatures, suggesting coherent emission mechanisms in extreme astrophysical processes. In this paper, we extend the bunched coherent Cherenkov radiation (CChR) framework by incorporating bunch inclination and geometric configuration parameters, enabling it to more rigorously model FRB emission and tera-Hertz (THz) emission from magnetars. When relativistic bunches are injected into the magnetized plasma of a magnetar’s magnetosphere at the Cherenkov angle, their emitted waves achieve phase coherence through constructive interference. Furthermore, the three-dimensional geometry of the bunches plays a crucial role in influencing the coherence of the radiation. Within the framework of CChR, we predict the existence of THz emission counterparts associated with FRBs and explain the observed characteristics of the THz-emitting magnetar SGR J1745-2900. Detections of such counterparts by upgraded millimeter telescopes (e.g., Atacama Large Millimeter/submillimeter Array, IRAM) would be expected to provide new insights into the potential physical connection between FRBs and magnetars.